Establishment of a protocol for the growth and multiplication of Setophoma terrestris and Fusarium spp. from an onion culture (Allium cepa L) - López-Courrau, Karol (2018)
Among the vegetables, the onion (Allium cepa L.) is the second largest consumed crop in the world and in 2015, Costa Rica planted approximately 1633.6 ha of onion. This production is affected by the presence of phytopathogens, especially fungi that attack roots such as Setophoma terrestris, which causes the disease known as pink root, and the fungi of the genus Fusarium spp. that causes basal rot. The objective of this research was to establish a protocol to optimize the growth of both fungi (S. terrestris and Fusarium spp.) in liquid medium, in order to facilitate their identification, manipulation and subsequent experimental works. Various physical parameters (pH, temperature, stirring speed and photoperiod) were evaluated and different culture media compositions were tested. The culture media analyzed in Fusarium spp. were potato dextrose homemade and commercial, oats, V8, SNA, Sabouraud dextrose and water. In addition, potato dextrose commercial and homemade, oats, vainica, minimum medium and water were tested for S. terrestris. Differences in treatments were determined using an analysis of variance and the Tukey test. This study demonstrated that Fusarium spp. grows optimally at 30 °C, pH 6, 100 rpm and darkness, and S. terrestris does at 28°C, pH 4, 100 rpm. In this fungus, growth under darkness stimulated biomass gain whereas light incidence resulted in reproductive phase establishment. The ideal medium for S. terrestris was the vainica for reproduction and homemade potato dextrose for vegetative growth, meanwhile for Fusarium spp. homemade dextrose potato medium was optimal for both processes.